RANCANG BANGUN ALAT PENGERING BUAH PINANG DENGAN METODE KANSEI ENGINEERING DAN DESAIN EKSPERIMEN DI DESA SUNGAI BEREMBANG KABUPATEN KUBURAYA - -, FIRMANSYAH - (Jurnal TIN Universitas Tanjungpura, 2017)
- Areca nut is a species of palm that grows in the area of West Borneo. Areca nuts drying is still carried out manually or traditional farmers. High water levels in the areca nut when dried by drying takes up to more than 15 days, Based on the problems faced by farmers in the drying process traditional areca nut. Thus, one alternative that can be done is through the design of the dryer areca nuts. The design tool nut dryer is based on the desire and emotion users. Desires and emotions are used as a reference to the characteristics of the product, and then will do the testing process. The method will be used to capture the desires and emotions by using the method and the method of Kansei Engineering Design Experiment to test the design. The results of the design tool areca nut dryer using kansei engineering methods in accordance with the wishes of consumers, obtained form the framework of a mixture, in blue, with iron made, with a medium-size, automatic functions, and the system is working with the oven with hot air. the experimental results by the method of Experimental Design in the dryer showed that the areca nut at a temperature of 45 Â° C with a 16-hour drying time can produce fruit perfectly dry, While the speed of the hot air blowing at the speed level 2 is level better speed, because at the speed level can produce a more stable temperature heating. Keywords: Areca, design, Design of Experiments, Dryer, Kansei Engineering